2015
DOI: 10.2351/1.4906622
|View full text |Cite
|
Sign up to set email alerts
|

Active reduction of waviness through processing with modulated laser power

Abstract: A new approach to the reduction of the waviness of metal surfaces is based on laser remelting with modulated laser power. Waviness reduction is reached due to the modification of direction of solidification of a molten pool. The changes of the molten pool are induced by laser radiation in which amplitude is modulated in accordance with initial topography of surface. The laser process with modulated laser power allows decreasing the waviness up to 80%-95% depending of the wavelength of the initial structure. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…According to Bordatchev [ 25 ], potential applications of the technology are the structuring of moulds for the production of light guides and texturing metal surfaces. An approach for removing waviness was considered by Oreshkin Reference [ 26 ]; the principle is called destructive interference.…”
Section: State Of the Artmentioning
confidence: 99%
“…According to Bordatchev [ 25 ], potential applications of the technology are the structuring of moulds for the production of light guides and texturing metal surfaces. An approach for removing waviness was considered by Oreshkin Reference [ 26 ]; the principle is called destructive interference.…”
Section: State Of the Artmentioning
confidence: 99%
“…Due to the extremely tiny beam diameter (<100 µm [214]) and tens of microseconds pulse duration [200], the existence time of laser formed micron molten pool (molten depth less than 6 µm [223]) is very short, and the fused material has solidified before the forming of next molten pool. For the spatial wavelength of initial surface roughness δ < 80 µm, CWLP has little effect [188], while PLP can further reduce the roughness to nano-scale [205]. Xiao et al [220] successfully eliminated the rainbow pattern on monocrystalline silicon by nanosecond pulsed laser, as shown in figure 28, which was produced by ultraprecision cutting, and reduced the roughness to 0.6 nm.…”
Section: Types Of Lmpmentioning
confidence: 99%
“…Phefferkorn et al [223,229,232] systematically explored effect of pulse width on surface topography, and found that long pulse width can form larger molten pool, which can reduce low-frequency roughness better. Because of the longer duration of larger molten pool, if the laser frequency is further increased until the pulse interval is less than molten pool duration, the continuous melting process will become a quasicontinuous melting process [205]. Laser diameter decreases with the increase of defocus amount [203,235,236].…”
Section: Machining Characteristics Of Lmpmentioning
confidence: 99%
“…Kuisat et al [8] found even for the direct laser interference patterning (DLIP on Ti64 and Scalmalloy©) process using ns laser pulses that this smoothing effect is inherent to the remelting process and occurs simultaneously to the DLIP process. This is similar to the WaveShape process, which achieves structuring and polishing in one process step [23] or even utilizes a spatially adapted laser power modulation for the reduction of waviness on a surface (Oreshkin et al [24]). Overall, the laser polishing process can be seen as a spatial low-pass filtering of a surface [25,26], resulting in an effective reduction of surface roughness.…”
Section: Introductionmentioning
confidence: 99%